The contextualization of science teaching: overview (Research, Society and Development, 2020)
The usage of the contextualization in Science teaching can be characterized as a current and pertinent theme in education that through the years aggregates several ways of interpretation and appliance, besides several points of view, to educational process. Therefore, the present research aims to promote a rescue of this subject, searching to elicit the main conceptions about what contextualizing in Science teaching is and what it is about, as exhibit the most relevant orientations about contextualization in the Common Curricular National Basis, the latest normative document of great value in Basic Education. To reach this objective, a qualitative, bibliographic and documental research was done, together with books and thesis and dissertations and scientific articles and official documents from the Federal Government, obtaining as a result, convergences and peculiarities in different analyzed sources. The expected result is for the study to serve also as a heading for studies and analyzes by the educators in order to reach an education closer and more attractive for the students.